STRATEGI PENGEMBANGAN KOMPETENSI GURU DI DAERAH TERTINGGAL - Reresi , Marsianus; Lamatokan, Jeisinta (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2023)
This research is a library research which aims to analyze and describe teacher competency development strategies in underdeveloped areas. The research method used is descriptive research. The author uses descriptive research by emphasizing the power of analysis of available sources and data by relying on theories and concepts to be interpreted and described which lead to the focus of the discussion. The results of the study found that the condition of education in disadvantaged areas requires more teachers who have pedagogical competence. Teachers who have pedagogical competence will be able to manage learning well, so that the teaching and learning process can take place effectively and the expected goals can be achieved. Therefore, to develop teacher pedagogic competence, an effective development strategy is needed through collaboration between various interested parties, namely the government, schools, teachers and the local community.